1995
DOI: 10.1037/0882-7974.10.2.248
|View full text |Cite
|
Sign up to set email alerts
|

Classical conditioning in patients with Alzheimer's disease: A multiday study.

Abstract: Previous studies demonstrated that patients with Alzheimer's disease (AD) do not acquire the classically conditioned eyeblink response. These studies, however, were only tested over a single conditioning session and, hence, raise the question of whether AD patients are capable of acquiring the response if sufficient training is given. This question may be of some importance whether AD patients can ultimately acquire the response has implications for the underlying neurobiological deficit in disrupted condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
1

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 33 publications
1
17
1
Order By: Relevance
“…Thus, the use of the trace eyeblink conditioning task is especially illuminating in this context, because it is also dependent on the hippocampus, as well as cholinergic function. Finally, EB conditioning is also impaired in patients with early Alzheimer's disease (Woodruff-Pak et al 1990;Solomon et al 1995;Woodruff-Pak 2001). The present results thus indicate that galantamine might be an especially good therapeutic agent for delaying the onset of the devastating learning and memory problems associated with Alzheimer's disease and mixed dementia (Alzheimer's disease with cerebrovascular disease), and has in fact been shown to be efficacious in this …”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, the use of the trace eyeblink conditioning task is especially illuminating in this context, because it is also dependent on the hippocampus, as well as cholinergic function. Finally, EB conditioning is also impaired in patients with early Alzheimer's disease (Woodruff-Pak et al 1990;Solomon et al 1995;Woodruff-Pak 2001). The present results thus indicate that galantamine might be an especially good therapeutic agent for delaying the onset of the devastating learning and memory problems associated with Alzheimer's disease and mixed dementia (Alzheimer's disease with cerebrovascular disease), and has in fact been shown to be efficacious in this …”
Section: Discussionmentioning
confidence: 72%
“…Certain kinds of Pavlovian EB conditioning tasks have proven to be a sensitive index of simple associative learning processes often disrupted in both aging organisms (e.g., Powell 1999) and various types of brain dysfunction including Alzheimer's disease (AD; Solomon et al 1991Solomon et al , 1995Woodruff-Pak and Papka 1996;Woodruff-Pak et al 1996a,b), Korsakoff's disease , schizophrenia (Sears et al 2000), and post-traumatic stress disorder (PTSD; Rasmusson and Charney 1997). Previous studies have demonstrated that treatment with 3.0 mg/kg GAL can significantly improve simple-delay eyeblink (EB) conditioning in older rabbits (Woodruff-Pak and Santos 2000;Woodruff-Pak et al 2001).…”
mentioning
confidence: 99%
“…In probable AD, there is very limited eyeblink conditioning in the first session of testing. However, when given a sufficient number of training trials (eg, 4 or 5 days of 90-trial presentations), patients diagnosed with probable AD acquire CRs [58,59]. This slowing of the rate of acquisition occurs in animal models when antagonists to cholinergic neurotransmission are introduced [39,60].…”
Section: Eyeblink Classical Conditioning In Alzheimer's Diseasementioning
confidence: 99%
“…There is a general consensus that this learning impairment is due to a true associative de® cit and is not caused by age-related di erences in responsivity to the conditioned or unconditioned stimulus (i.e., CS or US). Recent studies have demonstrated that the EB conditioned re¯ex is also impaired in patients with degenerative diseases of old age such as Alzheimer's disease (e.g., Solomon et al, 1995 ;Woodru -Pak, Finkbiner & Sasse, 1990).…”
mentioning
confidence: 99%
“…A question of considerable interest is thus whether age-related EB conditioning de® cits are related to a cerebellar or limbic system substrate (Powell, Buchanan, & Herna  ndez, 1991 ;Woodru -Pak, 1990). Some studies point toward a possible cerebellar focus while others point toward hippocampal participation in these de® cits (Woodru -Pak & Thompson, 1988b ;P apka, Ivry, & Woodru -P ak, 1995 ;Solomon et al, 1995 ;M oyer & Disterhoft, 1994 ;Thompson, M oyer, & Disterhoft, 1996). An important aspect of the age-related de® cits observed in EB classical conditioning is that it is due to the fact that a larger number of the elderly fail to show conditioning compared to younger people, rather than simply slower acquisition in the elderly.…”
mentioning
confidence: 99%